National roll-out of latent tuberculosis testing and treatment for new migrants in England: a retrospective evaluation in a high-incidence area. Issue 1 (11th January 2018) - Loutet, Miranda G.; Burman, Matthew; Jayasekera, Nivenka; Trathen, Duncan; Dart, Susan; Kunst, Heinke; Zenner, Dominik
Latent tuberculosis infection (LTBI) screening is an important intervention for tuberculosis (TB) elimination in low-incidence countries and is, therefore, a key component of England's TB control strategy. This study describes outcomes from a LTBI screening programme in a high-incidence area to inform national LTBI screening in England and other low-incidence countries. We conducted a retrospective cohort study of LTBI screening among eligible migrants (from high-incidence countries and entered the UK within the last 5 years), who were identified at primary-care clinics in Newham, London between August 2014 and August 2015. Multivariable logistic regression was used to identify factors associated with LTBI testing uptake, interferon-γ release assay (IGRA) positivity and treatment uptake. 40% of individuals offered LTBI screening received an IGRA test. The majority of individuals tested were 16–35 years old, male and born in India, Bangladesh or Pakistan. Country of birth, smoking status and co-morbidities were associated with LTBI testing uptake. IGRA positivity was 32% among those tested and was significantly associated with country of birth, age, sex and co-morbidities. This study identifies factors associated with screening uptake, IGRA positivity and treatment uptake, and improves understanding of groups that should be supported to increase acceptability of LTBI testing and treatment in the community. The LTBI screening programme is effective in identifying a high number of LTBI cases, but it is patient and provider-dependent http://ow.ly/AKMu30g1rMB